Monolingual dictionaries for advanced learners of English: an analysis of the definitions of the adjective 'surprising' and its synonyms - doi: 10.4025/actascilangcult.v35i4.17857 - Andrelino, Paulo José (2013)
Monolingual dictionaries are lexicographic references greatly used by students of English. New updated editions frequently appear on the market. One of the main reasons for the dictionary’s use is the search for word meanings during decoding and encoding activities. Employing the criteria of comprehensibility devised by Bogaards (1996), which involves the defining vocabulary, the type and the precision of definitions, current research compares the definitions of the adjective ‘surprising’ and its synonyms among three monolingual English dictionaries for advanced learners of English: Collins COBUILD Advanced Dictionary of American English, Longman Dictionary of Contemporary English, and Oxford Advanced Learner’s Dictionary. The above lexical item was selected for comparison because it appeared in a dictionary usage activity within the classroom. In such activity, the prospective teachers were invited to approach the use of the adjective and its synonyms, in specific contexts of use. Results show that, due to the particular style of each dictionary concerning the presentation of information in the microstructure, more studies on other aspects of these books might be undertaken to obtain a clearer understanding of how they deal with definitions in their microstructure.